The Role of Ethnicity and Board Diversity in Corporate Performance: Cases of Kompas 100 Indexed Companies - Alga Aprila Dwi Purwito; , Sutrisno (Journal of Business and Management Review, 2024)
Research Aims: The main objective of this study is to examine the role of ethnicity in board (EoB) on corporate performance. In addition, it also examines the effect of board diversity consisting of foreign in board (FoB), women in board (WoB), board of directors (BoD), board of commissioners (BoC), and board of independent commissioners (BoCI) on corporate performance. Corporate performance consists of financial performance as measured by return on assets (ROA) and market performance as measured by Tobin's Q. Design/methodology/approach: The population in this study were companies listed on the Kompas 100 Index on the Indonesia Stock Exchange with a sample of 55 companies taken using purposive sampling techniques. The observation period was five years (2019-2023). Hypothesis testing using panel data regression. After conducting the Chow-test, Hausman-test and LM-test, the best model was panel data regression with a fixed effect model.. Research Findings: The results of the study using the fixed effect model show that ethnic on board and women on board do not affect corporate performance, while foreign on board has a significant positive effect on corporate performance, both as measured by ROA and Tobin's Q. The results of the study also show that the board of directors does not affect corporate performance, while the board of independent commissioners has a significant positive effect on corporate performance, while the board of commissioners has a significant effect but with a negative coefficient. Theoretical Contribution/Originality: This research provides a scientific contribution that can be utilized by further researchers who focus on issues of board structure and board diversity. Keywords: ethnicity on board, women on board, foreign on board, board of director, board of independen commssionioners